Disaster Mitigation and Emergency Response in the School Environment - Rohani; Tina Rahmawati (Postgraduate, University of Mataram, 2025)
Natural disasters are a significant threat in vulnerable areas, including Indonesia which frequently experiences floods, earthquakes, and landslides. This study explores disaster mitigation and emergency response management in schools in Sembakung and Lumbis Districts, Nunukan Regency. The objectives are to understand the challenges, human resource (HR) readiness, availability of facilities and infrastructure, community participation, technology utilization, and post-disaster psychosocial support. Qualitative methods were used with in-depth interviews with school principals, teachers, and staff. The findings show limited disaster mitigation and simulation training, minimal disaster-resistant school infrastructure, and low community participation and technology limitations in remote areas. This study recommends a holistic approach to improving disaster preparedness through training, infrastructure strengthening, community participation, technology utilization, and psychosocial support. Collaboration between government, schools, and local communities is needed to create a safe and resilient educational environment in the face of disasters.